(untitled) (The Review of Diabetic Studies, 2025)
Simulation-based learning (SBL) has emerged as an innovative educational approach in nursing, offering students opportunities to bridge theoretical knowledge with practical application in a safe, controlled environment. Nursing education faces the dual challenge of developing clinical competence and fostering confidence among students, both of which are critical for effective patient care and professional readiness. This systematic review aimed to evaluate the effectiveness of simulation-based learning in enhancing nursing students’ clinical competence and confidence. A comprehensive literature search was conducted across PubMed, CINAHL, Scopus, and Google Scholar for articles published between 2010 and 2025. Inclusion criteria were empirical studies assessing simulation interventions targeting competence and confidence in undergraduate or graduate nursing students. A total of 32 studies met the eligibility criteria and were critically appraised using the Joanna Briggs Institute (JBI) checklist for systematic reviews. Findings indicated that simulation significantly improves clinical competence by enhancing knowledge retention, psychomotor skill acquisition, critical thinking, and decision-making abilities. High-fidelity simulations, in particular, were associated with better outcomes compared to low-fidelity or traditional teaching methods. Simulation-based training also contributed to improved confidence levels, with students reporting reduced anxiety, improved self-efficacy, and enhanced readiness for clinical practice. Furthermore, repeated exposure to simulation exercises with structured debriefing demonstrated stronger, sustained learning outcomes. Although the evidence strongly supports the integration of SBL in nursing curricula, challenges such as high cost, faculty training requirements, and resource limitations were frequently reported. Future research should focus on longitudinal outcomes, cost-effectiveness, and the integration of simulation into competency-based curricula.Simulation-based learning plays a pivotal role in strengthening both competence and confidence in nursing students. Its integration into nursing education can foster safe, effective, and confident future practitioners, ultimately improving patient care outcomes.